ERPs and their brain sources in perceptual and conceptual prospective memory tasks: Commonalities and differences between the two tasks. (October 2016) - Cruz, Gabriela; Miyakoshi, Makoto; Makeig, Scott; Kilborn, Kerry; Evans, Jonathan
Abstract: The present study examined whether Event-Related Potential (ERP) components and their neural generators are common to perceptual and conceptual prospective memory (PM) tasks or specific to the form of PM cue involved. We used Independent Component Analysis (ICA) to study the contributions of brain source activities to scalp ERPs across the different phases of two event-based PM-tasks: (1) holding intentions during a delay (monitoring) (2) detecting the correct context to perform the delayed intention (cue detection) and (3) carrying out the action (realisation of delayed intentions). Results showed that monitoring for both perceptual and conceptual PM-tasks was characterised by an enhanced early occipital negativity (N200). In addition the conceptual PM-task showed a long-lasting effect of monitoring significant around 700 ms. Perceptual PM-task cues elicited an N300 enhancement associated with cue detection, whereas a midline N400-like response was evoked by conceptual PM-task cues. The Prospective Positivity associated with realisation of delayed intentions was observed in both conceptual and perceptual tasks. A common frontal-midline brain source contributed to the Prospective Positivity in both tasks and a strong contribution from parieto-frontal brain sources was observed only for the perceptually cued PM-task. These findings support the idea that: (1) The enhanced N200 can be understood as a neural correlate of a 'retrieval mode' for perceptual and conceptual PM-tasks, and additional strategic monitoring is implemented according the nature of the PM task; (2) ERPs associated with cue detection are specific to the nature of the PM cues; (3) Prospective Positivity reflects a general PM process, but the specific brain sources contributing to it depend upon the nature of the PM task. Highlights: The N200 in conceptual and perceptual PM-tasks is a correlate of monitoring. A long lasting ERP effect reflects monitoring only for the conceptual PM-task. ERPs associated with cue detection are specific to the nature of the PM cue. The Prospective Positivity arises from a mix of parieto-frontal sources in both PM-tasks. The Anterior Cingulate Cortex is common to the prospective positivity in both tasks.